Project-Based Learning dalam Meningkatkan Pemahaman Al-'Alim, Al-Khabir, Al-Sami’, dan Al-Basir Siswa Kelas VII SMPN 24 Batanghari - Lestari, Puji; Noprianti, Noprianti; Santriawati, Santriawati (ISLAMIKA, 2024)
This study evaluates the effectiveness of implementing Project-Based Learning (PjBL) in enhancing creativity and collaboration among seventh-grade students in Islamic Religious Education Al-’Alim, Al-Khabir, Al-Sami material at SMPN 24 Batanghari. Although the research instrument showed inadequate reliability (Cronbach's Alpha 0.504), statistical tests revealed that the PjBL model had a positive impact on student learning outcomes. The posttest t-test indicated a significant difference between the experimental and control classes, with the experimental class showing higher average posttest scores. While the Anova test did not show significant average differences between the two groups, the PjBL model demonstrated improvements in student creativity and collaboration in the experimental class. This study highlights the potential of PjBL in enhancing IRE education and recommends further research to refine the instruments and methodologies used.